Nutritional condition determines behavioral response of nestling Black-browed albatrosses to a shy-bold continuum test. Issue 3 (4th May 2019) - Morandini, Virginia; Ferrer, Miguel
Abstract : We used biochemical analyses of blood to quantify nutritional status and a standardized test to measure the response to a novel object (bold-shy test). Our aim was to examine the relationship between nutritional status and behavioral responses in nestlings of Black-browed albatrosses ( Thalassarche melanophrys ). A total of 66 nestlings from Saunders Island (Falkland) were analyzed. Around 41% of the differences in the intensity of responses (number of peaks per 1 min) were explained by the age and physiological conditions of the individual. Blood urea levels alone explained more than 28% of differences in number of pecks per minute. Nutritional condition can be a confounding factor when we study behavioral responses using a typical bold-shy test. Our results encourage other authors to be more cautious when designing experiments and to take into account the potential effect of nutritional level and age as potential partial explanations of individual behavioral responses.